Methods to improve medication adherence in patients with chronic inflammatory rheumatic diseases: a systematic literature review. Issue 2 (27th July 2018) - Lavielle, Matthieu; Puyraimond-Zemmour, Déborah; Romand, Xavier; Gossec, Laure; Senbel, Eric; Pouplin, Sophie; Beauvais, Catherine; Gutermann, Loriane; Mezieres, Maryse; Dougados, Maxime; Molto, Anna
Abstract : Objective: Lack of adherence to treatment is frequent in chronic inflammatory rheumatic diseases and is associated with poorer outcomes. The objective of this study was to describe and evaluate interventions that have been proposed to enhance medication adherence in these conditions. Methods: A systematic literature review was performed in Pubmed, Cochrane, Embase and clinicaltrials.gov databases completed by the rheumatology meeting (ACR, EULAR and SFR) abstracts from last 2 years. All studies in English or French evaluating an intervention to improve medication adherence in chronic inflammatory rheumatic diseases (rheumatoid arthritis (RA), spondyloarthritis (SpA), crystal related diseases, connective tissue diseases, vasculitis and Still's disease) were included. Interventions on adherence were collected and classified in five modalities (educational, behavioural, cognitive behavioural, multicomponent interventions or others). Results: 1325 abstracts were identified and 22 studies were finally included (18 studies in RA (72%), 4 studies in systemic lupus erythematosus (16%), 2 studies in SpA (8%) and 1 study in gout (4%)). On 13 randomised controlled trials (RCT) (1535 patients), only 5 were positive (774 patients). Educational interventions were the most represented and had the highest level of evidence: 8/13 RCT (62%, 1017 patients) and 4/8 were positive (50%). In these studies, each patient was individually informed or educated by different actors (physicians, pharmacists, nurses and so on). Supports and contents of these educational interventions were heterogenous. Conclusion: Despite the importance of medication adherence in chronic inflammatory rheumatic disorders, evidence on interventions to improve medication adherence is scarce.